2014
DOI: 10.3390/nu6125772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tea Theaflavins and Catechins on Microvascular Function

Abstract: Beneficial effects of flavonoid-rich black and green tea on macrocirculation have been well established. Theaflavins are unique to black tea as they are formed from catechins during the enzymatic oxidation of tea leaves. The study was performed to gain more insight into the effects of theaflavins on microcirculation and to compare effects with another important flavonoid class, the green tea derived catechins, which have been reported to improve vascular function. Twenty-four healthy subjects were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…This expands on earlier findings by Fuchs et al (2014) who reported significant improvements in hyperaemia following a 12-day intervention.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…This expands on earlier findings by Fuchs et al (2014) who reported significant improvements in hyperaemia following a 12-day intervention.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…Although cardiovascular risk biomarkers were assessed at 5 h after intake, which is the anticipated peak flavanone plasma concentration [based on previous flavanone pharmacokinetic data ( 15 )], it remains possible that beneficial cardiovascular effects could have been observed after a more prolonged (5–24 h or several weeks/mo) exposure. In addition, the present study used the RH-PAT index to measure fingertip endothelial function, and although flow-mediated dilatation of the brachial artery is generally accepted as a more sensitive method of assessing endothelial function ( 37 ) and CVD risk ( 38 ), an improvement in the RH-PAT index has recently been observed after an acute flavonoid intervention ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…14,15) Fuchs et al (2014) reported that theaflavin administration increased peripheral microcirculation. 16) In addition, single oral administration of theaflavins significantly increased energy expenditure and upregulated uncoupling protein-1,3 and peroxisome proliferator-activated receptor gamma coactivator-1α in brown adipose tissue. 17) These results raised the possibility that black tea polyphenols reduced lipid absorption in the intestine and activated energy consumption by upregulating metabolic genes, resulting in reduced body fat.…”
Section: Discussionmentioning
confidence: 98%